2011
DOI: 10.4085/1062-6050-46.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Risk of Anterior Cruciate Ligament Injury Among Sportswomen in Slovenia

Abstract: Context: Anterior cruciate ligament (ACL)-injury rate is greater among female athletes than among male athletes.Objective: To investigate the rate and risk of ACL injury among Slovenian sportswomen playing professional basketball, team handball, or volleyball.Design: Prospective cohort study. Main Outcome Measure(s): We asked sportswomen and coaches to document the occurrence of every significant traumatic knee injury requiring medical attention. Injury rate and injury risk were calculated for sportswomen in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…Unfortunately, most of the studies were scored moderate and thus a major part of the found studies are not represented in the results. It was hard to compare and represent the findings in one figure or as one result, since different studies reported the outcome in different descriptive injury rates, such as injuries per 1000 hours per player Bere et al, 2015;Verhagen et al, 2004Verhagen et al, , 2005, injuries per 1000 hours exposure Bahr et al, 2003;Vauhnik et al, 2011), injuries per 10,000 exposures and injuries per 1000 athlete exposures (Barber Foss et al, 2014). Ideally, all studies should use the same descriptive injury rates to enable studies and their results to be compared with each other.…”
Section: Methodological Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, most of the studies were scored moderate and thus a major part of the found studies are not represented in the results. It was hard to compare and represent the findings in one figure or as one result, since different studies reported the outcome in different descriptive injury rates, such as injuries per 1000 hours per player Bere et al, 2015;Verhagen et al, 2004Verhagen et al, , 2005, injuries per 1000 hours exposure Bahr et al, 2003;Vauhnik et al, 2011), injuries per 10,000 exposures and injuries per 1000 athlete exposures (Barber Foss et al, 2014). Ideally, all studies should use the same descriptive injury rates to enable studies and their results to be compared with each other.…”
Section: Methodological Aspectmentioning
confidence: 99%
“…Of the 28 included studies concerning the incidence and prevalence of musculoskeletal injuries among volleyball players (data extraction in Table I), eight studies were scored with a low risk of bias Barber Foss et al, 2014;Bere et al, 2015;de Loes et al, 2000;Junge et al, 2006;Vauhnik et al, 2011;Verhagen et al, 2004) and 20 with a moderate risk of bias Beneka et al, 2009Beneka et al, , 2007Beynnon et al, 2014;Fernandez et al, 2007;Kujala et al, 1995;Lanese et al, 1990;Malliou et al, 2008;Rechel et al, 2011;Reeser et al, 2015;Robinson et al, 2014;Solgard et al, 1995;Swenson et al, , 2013Tsigganos et al, 2007;. The incidence and prevalence of musculoskeletal injuries among volleyball players from the studies with a low risk of bias are presented in Figure 1.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Vauhnikas su bendraautoriais, išnagrinėjęs įvairių sporto šakų sportininkų ypatumus, nurodė, kad aukštesni sportininkai dažniau patiria traumas nei žemesnio ūgio sportininkai (Vauhnik et al, 2011). Rankinio sporto šakoje traumos sietinos su netinkamu fiziniu pasirengimu (Luig, Henke, 2010).…”
Section: įVadasunclassified
“…This excessive force exerted on the ACL can cause ligament rupture, with females reported to be up to eight times more likely to suffer an ACL injury in comparison with males . Subsequently, ACL annual injury risk in female court athletes (up to 7.3% of surveyed population suffering a current ACL injury) is some of the highest reported when compared to variety of sporting populations . The speculated reasons why females are at an increased risk of injuring their ACL include hormonal and anatomical factors which affect the rigidity of the ACL …”
Section: Introductionmentioning
confidence: 99%